A qualitative analysis of people's experiences with weight-based discrimination. Issue 9 (8th August 2022) - Gerend, Mary A.; Patel, Shefali; Ott, Nicholas; Wetzel, Karen; Sutin, Angelina R.; Terracciano, Antonio; Maner, Jon K.
Abstract: Objective: The aim of this study was to describe people's day-to-day experiences with weight-based discrimination and to distill themes that shed new light on this phenomenon. Design: A qualitative study was conducted in 2019 using a purposive sampling strategy. A racially and ethnically diverse sample of 32 U.S. adult men and women with a body mass index ≥30 kg/m 2 completed a semi-structured interview. Results: Primary types of interpersonal weight-based discrimination included offensive comments, negative assumptions, social rejection, and unwanted attention or bullying. Participants also encountered environmental sources of weight bias such as inadequate seating in public venues. Three higher order themes that cut across people's experiences with weight-based discrimination were identified: 1) the often-ambiguous nature of weight-based discrimination; 2) intersections between body weight and other social identities; and 3) the role of social comparison processes. Conclusion: Findings provide a detailed portrait of people's everyday experiences with weight-based discrimination. These experiences often reflected widely held negative stereotypes about people with higher body weight and conveyed the socially devalued status of higher-weight individuals in society. Findings have important implications for future research and interventions aimed at reducing the harmful effects of weight-based discrimination on health and emotional wellbeing.